Experimental Study of Enlarged Base Pile under Tension Load in Sand - Ahmed nasr; Wasiem Azzam; Ahmed abd Elgwad (Journal of Engineering Research - Egypt)
Important aspects of foundation design include developing an understanding of the behaviour of enlarged base piles and aiming to predict their capacities when subjected to uplift loads. On single enlarged base piles implanted in cohesionless soil and subjected to pure tension loading, model experiments have been done. In a steel soil tank, the tests were carried out on straight-shafted vertical steel piles with an outside diameter (Do) of 25mm and inner diameter (Di) of 19mm, base diameter (Db) of 50mm and base angle (θ) of (45◦). The embedment length-to-base diameter ratios (L/Db) of the studied piles are 5, 6, 8, and 12. The relative density of 30%, 50%, and 80% are used to prepare the sand bed. The effect of pile embedment depth and relative soil density on the uplift loads is examined. The investigation showed that the behaviour of single enlarged base piles under uplift loading is mostly determined by the ratio of pile embedment length to base diameter and soil parameters. Using the base at the end of piles significantly increases their uplift capacity, according to the study's findings.